Le contrôle de l’assurance au Canada - Humphrys, Richard (Assurances)

(untitled) (HEC Montréal, 1981)
In this survey of Insurance control in Canada, the Superintendent of Insurance deals with the supervision of Insurance Companies and their technical and financial problems in Canada. For lack of space, we had to publish his paper in two parts. This one presents the main concerns of the Superintendent regarding the problems of the insurance companies coming under his supervision. In periods of inflation, the inherent difficulties of insurance take an increased importance which does impose upon the Superintendent of Insurance new and wider responsibilities. A.